Antibiotic Elution from Hip and Knee Acrylic Bone Cement Spacers: A Systematic Review - Konstantinos Anagnostakos (BioMed Research International, 2017)
Knowledge about the elution from antibiotic-loaded cement spacers is an indispensable premise for guarantee of clinical success. A systematic literature search was performed through PubMed. Search terms were “antibiotic elution” and “antibiotic release” in combination with “spacer,” “hip spacer,” and “knee spacer,” respectively. A total of 11 studies could be identified. Seven studies reported on the release of antibiotics after spacer implantation, three studies at spacer removal, and one study on both time points. Seven studies reported on hip spacers, one study on knee spacers, and three studies on both. In eight studies, custom-made spacers have been implanted and in three prefabricated ones. In the majority of the studies, the cement has been loaded with an antibiotic combination, mostly consisting of aminoglycoside (either gentamicin or tobramycin) and vancomycin. Measured concentrations exceeded the minimal inhibitory concentration of the particular pathogen organisms in each case. However, large discrepancies were observed with regard to the height of the antibiotic concentration depending on the antibiotic combination and the antibiotic ratio used. Current literature data indicate a sufficient elution of antibiotics after spacer implantation and at spacer removal, respectively. Future studies are required to optimize the local antibiotic therapy at the site of spacer implantation.